The influence of tooth brushing supervision on the dental plaque index and toothbrush wear in preschool children - Letícia Maíra Wambier; Gisele Dias; Priscila Bittar; Márcia Thaís Pochapski; Denise Stadler Wambier; Ana Cláudia Rodrigues Chibinski; Fábio André dos Santos
OBJECTIVE: To evaluate the effectiveness of tooth brushing supervision in one or more sessions on dental plaque removal and toothbrush wear. MATERIAL AND METHOD: 3- to 5-year-old children received new toothbrushes and attended a puppet theater about oral health. Forty-nine children were randomly selected and divided into 3 groups (GI=20; GII=14; GIII=14). Fones' brushing method was demonstrated to the GI and GII groups to evaluate the following: the professional direct supervision and tooth brushing training in five sessions (GI), the professional direct supervision and a one-training session (GII) and the puppet theater influence only (GIII-control group). The dental plaque index (IPL) was recorded at baseline (T0), after 24 days (T1) and after 46 days (T2) and toothbrush wear (ID) was recorded on T1 and T2. The Kruskal-Wallis test and the Friedman test (IPL), as well as the one-way ANOVA and the paired Student's t-test (ID) (p<0.05) were employed to analyze the data. RESULT: GI showed a significant difference from the others groups in T1 and T2 (p<0.01).The index of toothbrush wear increased (p<0.0001) from 24 days (0.52±0.35mm) to 46 days (0.90±0.48mm), but there was no significant association between toothbrush wear and plaque index for T1 (r=0.230-p= 0.116) as well as for T2 (r=0.226-p=0.121). CONCLUSION: The multiple sessions of professional supervision were effective to reduce the dental plaque index, which was not influenced by toothbrush wear, showing continuous oral hygiene motivation needs.